VALUE-BASED LEADERSHIP AND CREATING A POSITIVE ORGANIZATIONAL CULTURE - Aprizal Ahmad; Riski Pranata Putra (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
Value-based leadership is essential for building a positive work culture, which can improve employee performance and satisfaction. Leaders can create a work environment that supports innovation and collaboration. By instilling values such as honesty, mutual respect, and responsibility, an effective leader can motivate and inspire team members to achieve business goals while also developing the character and integrity of each team member. When these values are adopted by all employees, they foster a strong sense of ownership and commitment to the company's vision and mission. The result is a positive organizational culture. This enhances productivity, reduces turnover rates, and boosts employee loyalty.